profile
Опубликовано - 2 месяца назад | По предмету Математика | автор Аноним

(2х-1) *(х+3)=0 2(х-3)=7(2-х) 3х-2=2х-3 5 4

  1. Ответ
    Ответ дан Беляков Петр

    1) (2х - 1) * (х + 3) = 0;

    n

    2х - 1 = 0;

    n

    2х = 1;

    n

    х = 1 : 2;

    n

    х1 = 1/2.

    n

    х + 3 = 0;

    n

    х2 = 0.

    n

    Ответ: х1 = 1/2; х2 = 0.

    n

     

    n

    2) 2(х - 3) = 7(2 - х);

    n

    2х - 6 = 14 - 7х;

    n

    2х + 7х = 14 + 6;

    n

    9х = 20;

    n

    х = 20 : 9;

    n

    х = 20/9 = 2 2/9.

    n

    Ответ: х = 20/9 = 2 2/9.

    n

    3) 3х - 2 = 2х - 3;

    n

    3х - 2х = -3 + 2;

    n

    х = -1.

    n

    Ответ: х = -1.

    0



Топ пользователи